Political continuity in Eritrea: Domestic and foreign policy considerations - Ylönen, A. (The Horn of Africa since 2018: Continuities, transformations, and prospects, 2025)
Eritrea has experienced remarkable political continuity since its liberation struggle. This chapter discusses the political continuity and highlights the persistence of the liberation mentality driving the national government and internal political developments. It also shows how Eritrea has navigated through political turbulence in its troubled neighborhood in the Horn of Africa. First, this chapter provides a brief geostrategic overview and a background to the politics of liberation in Eritrea. It then discusses the major events and trajectories of Eritrea's internal politics and foreign policy during the early independence. Finally, this chapter debates political continuity in the context of post-2018 rapprochement with Ethiopia. It concludes by emphasizing the legacy of resistance, resilience, self-sacrifice, and self-reliance, which continue to characterize the dynamics of Eritrean politics.